The use and value of fiction in Greek and Roman history - Muñiz Coello, J. (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2019)
Ancient Greeks and Romans knew about their past primarily through the epic poem. With the poetic resources typical of this genre, it went on to typify the way in which the historical report was made. In other words, both truth and fiction became elements giving form to the histories of Greek and Roman authors. In this paper, we explore the Roman historians’ attitudes in order to reconcile fiction with evidence, fable with fact and the consequences on the historical account.
Keywords: Fable; history; poetry; Livy; Dionysius of Halicarnassus